Analisis Usability BPRGianyar.com Menggunakan Heuristic Evaluation dan Pendekatan Human-Centered Design - I Putu Aris Richard Hernanda; Dwi Putra Githa; Gusti Made Arya Sasmita (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
BPR Gianyar Partasedana is a people's credit company that focuses on small businesses in the Gianyar Region it has a website containing various information on financial services. Since the website was first created, no evaluation has been carried out to determine user satisfaction and problems with the website. Usability evaluation on the user interface needs to be done in order to find out how users interact when using the website and find usability problems. The method used to conduct the test is Heuristic Evaluation, the analysis is carried out by interviews and questionnaires to obtain user data, and research samples are taken from customers or people who have used the BPR Gianyar website. Evaluation of the initial interface design shows usability problems with category 3 (major usability problem) so there are problems with the main usability. The Human-Centered Design approach is used as a basis for providing recommendations, the evaluation results on recommendations for interface design improvements show a decrease in the value of usability problems from category 3 to category 1 (cosmetic problem) so that it is better and there are no problems that interfere with the usability of the system. Keywords—Website, Usability, Heuristic Evaluation, Human-Centered Design